Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Ask your questions and receive precise answers from experienced professionals across different disciplines. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To find the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex] that satisfy the equation [tex]\(x^2 + 3x + 4 = (x + a)^2 + b\)[/tex], we'll follow these steps:
1. Expand the right-hand side of the equation [tex]\((x + a)^2 + b\)[/tex]:
[tex]\[ (x + a)^2 + b = x^2 + 2ax + a^2 + b \][/tex]
2. Set the expanded right-hand side equal to the left-hand side of the equation:
[tex]\[ x^2 + 3x + 4 = x^2 + 2ax + a^2 + b \][/tex]
3. Compare the coefficients of corresponding terms on both sides of the equation:
- The coefficient of [tex]\(x^2\)[/tex] is [tex]\(1\)[/tex] on both sides.
- The coefficient of [tex]\(x\)[/tex] on the left-hand side is [tex]\(3\)[/tex], and on the right-hand side it is [tex]\(2a\)[/tex].
- The constant term on the left-hand side is [tex]\(4\)[/tex], and on the right-hand side it is [tex]\(a^2 + b\)[/tex].
4. Equate the coefficients to form a system of equations:
- For the [tex]\(x\)[/tex] term:
[tex]\[ 2a = 3 \][/tex]
- For the constant term:
[tex]\[ a^2 + b = 4 \][/tex]
5. Solve the equation [tex]\(2a = 3\)[/tex] for [tex]\(a\)[/tex]:
[tex]\[ a = \frac{3}{2} \][/tex]
6. Substitute [tex]\(a = \frac{3}{2}\)[/tex] into the equation [tex]\(a^2 + b = 4\)[/tex] to find [tex]\(b\)[/tex]:
[tex]\[ \left(\frac{3}{2}\right)^2 + b = 4 \][/tex]
[tex]\[ \frac{9}{4} + b = 4 \][/tex]
[tex]\[ b = 4 - \frac{9}{4} \][/tex]
[tex]\[ b = \frac{16}{4} - \frac{9}{4} \][/tex]
[tex]\[ b = \frac{7}{4} \][/tex]
Therefore, the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex] that satisfy the equation are:
[tex]\[ a = \frac{3}{2} \quad \text{and} \quad b = \frac{7}{4} \][/tex]
1. Expand the right-hand side of the equation [tex]\((x + a)^2 + b\)[/tex]:
[tex]\[ (x + a)^2 + b = x^2 + 2ax + a^2 + b \][/tex]
2. Set the expanded right-hand side equal to the left-hand side of the equation:
[tex]\[ x^2 + 3x + 4 = x^2 + 2ax + a^2 + b \][/tex]
3. Compare the coefficients of corresponding terms on both sides of the equation:
- The coefficient of [tex]\(x^2\)[/tex] is [tex]\(1\)[/tex] on both sides.
- The coefficient of [tex]\(x\)[/tex] on the left-hand side is [tex]\(3\)[/tex], and on the right-hand side it is [tex]\(2a\)[/tex].
- The constant term on the left-hand side is [tex]\(4\)[/tex], and on the right-hand side it is [tex]\(a^2 + b\)[/tex].
4. Equate the coefficients to form a system of equations:
- For the [tex]\(x\)[/tex] term:
[tex]\[ 2a = 3 \][/tex]
- For the constant term:
[tex]\[ a^2 + b = 4 \][/tex]
5. Solve the equation [tex]\(2a = 3\)[/tex] for [tex]\(a\)[/tex]:
[tex]\[ a = \frac{3}{2} \][/tex]
6. Substitute [tex]\(a = \frac{3}{2}\)[/tex] into the equation [tex]\(a^2 + b = 4\)[/tex] to find [tex]\(b\)[/tex]:
[tex]\[ \left(\frac{3}{2}\right)^2 + b = 4 \][/tex]
[tex]\[ \frac{9}{4} + b = 4 \][/tex]
[tex]\[ b = 4 - \frac{9}{4} \][/tex]
[tex]\[ b = \frac{16}{4} - \frac{9}{4} \][/tex]
[tex]\[ b = \frac{7}{4} \][/tex]
Therefore, the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex] that satisfy the equation are:
[tex]\[ a = \frac{3}{2} \quad \text{and} \quad b = \frac{7}{4} \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.